2017
DOI: 10.3390/molecules22050812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mycobactericidal Effect of Thio-functionalized Carbohydrate Derivatives

Abstract: Sugars with heteroatoms other than oxygen have attained considerable importance in glycobiology and in drug design since they are often more stable in blood plasma due to their resistance to enzymes, such as glycosidases, phosphorylases and glycosyltransferases. The replacement of oxygen atoms in sugars with sulfur forms thio-sugars, which are potentially useful for the treatment of diabetes and some bacterial and viral infections. Here, we evaluated the antibacterial activity of thio-functionalized carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…It was recently reported that Mtb is sensitive to thio-functionalized carbohydrate derivatives, including thio-glycoside, thio-semicarbazone, aminothiazole and thiazoline [39]. Here, we found that the accumulation of mutations in the ppe51 gene affects the sensitivity of Mtb mutants to thio-glycoside (thio-disaccharide, T-6), which might be reversed by the introduction of an intact ppe51 gene into the mutants.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It was recently reported that Mtb is sensitive to thio-functionalized carbohydrate derivatives, including thio-glycoside, thio-semicarbazone, aminothiazole and thiazoline [39]. Here, we found that the accumulation of mutations in the ppe51 gene affects the sensitivity of Mtb mutants to thio-glycoside (thio-disaccharide, T-6), which might be reversed by the introduction of an intact ppe51 gene into the mutants.…”
Section: Discussionmentioning
confidence: 70%
“…We have recently shown that thio-functionalized carbohydrate derivatives such as thioglycoside, thiosemicarbazone, aminothiadiazole and thiazoline present bactericidal activity against tubercle bacilli, inhibiting their growth at concentrations below 100 µM/CFU. At micromolar concentrations, these compounds were not active against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus [39]. Here, we applied the compound T-6, thio-disaccharide (1,6-anhydro-3-deoxy-4-S-(2,3,4,6-tetra-O-acetyl-β-d-glucopyranosyl-d-glycero-hexopyranos-2-ulose), at a concentration MIC 50 = 50 µM/CFU, to inhibit the growth of Mtb and to identify proteins involved in the uptake of T-6-like compounds.…”
Section: Selection Of T-6 Resistant Mutantsmentioning
confidence: 93%
See 1 more Smart Citation
“…Synthetic thiosugars are effective inhibitors of numerous cellular enzyme pathways. Besides, numerous studies have shown their significant antimicrobial, antiviral, antithrombotic, and anticancer potential [ 33 , 34 , 35 , 36 ]. Therefore, increasingly sulfur derivatives of carbohydrates are used for the synthesis of new pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention has been given to antitubercolosis and antifungal derivatives. New promising antimycobacterial candidates emerged among a new set of carbohydrate derivatives studied by Korycka-Machala et al [ 6 ]. Starting from the consideration that sugars with heteroatoms other than oxygen have attained considerable importance in glycobiology and in drug design due to their resistance to enzymes such as glycosidases, phosphorylases and glycosyltransferases, the authors screened a set of 21 thio-functionalized carbohydrate derivatives against acid-fast Mycobacterium tuberculosis (Mtb) and several other bacteria.…”
mentioning
confidence: 99%